Limitações e possibilidades da gestão orientada para resultados: um estudo de caso da implementação do Programa de Controle de Enchentes na prefeitura da cidade do Rio de Janeiro - Oliveira, Sérgio Nunes de (2008)
During the months of july and august of 2005, the Program of Prevention and Flood Control, of the city hall of Rio de Janeiro city, was object of a procedure of operational auditorship It was carried through by a team of technicians of the Court of Accounts of Rio de Janeiro city - TCMRJ. The main purpose of this auditorship was the evaluation of the implementation and management process concerning the program, during the period 2002-2005, according to economy, efficiency, effectiveness and effectiveness criteria on the resources application. The auditors had pointed out imperfections in the planning and implementation process, characterized basically by problems concerning contracts execution and the fulfillment of the goals defined in the program planning. Although the problems pointed out and the register of some recommendations on chances of management improvement, the general conclusion brought up by the report was of that it was not possible to evaluate consistently the efficiency and the effectiveness ofthe programo However, the results gathered by the present analysis had disclosed that the problems pointed out by the study of the TCMRJ refered to deepest causes, those related to the dynamics of the process of public politics formulation and implementation. Those dynamics nor always presents elements lined up with the demanded characteristics and structural requirements for the proper working of the performance management mode!. In this line of development, this study aimed to organize the collected evidences by the TCMRJ auditorship among a analysis structure able to relate the pointed out problems to its causative factors. The methodological validity of the TCMRJ work is not questioned here, but to put it in front of a perspective of more structured analysis and in face of its real object of analysis: the model of management guided by results - its characteristics, requirements and limitations.